Needle Geometry, Target Migration and Substrate Interactions in High Resolution - Oldfield,M; Leibinger,A; Kaufmann,P-A; Bertucchi,M; Beyrau,F; Rodriguez,y Baena F (IEEE, 2014)
Recent investigations considering flexible, steerableneedles for minimally invasive surgery have shown thesignificance of needle shape in determining the needle-tissueinteractions leading to the access of targets. Digital ImageCorrelation has enabled internal deformation and strain causedby needle insertions to be seen in a soft tissue phantom at highresolution for the first time. Here, the impact of tip designon strains and displacements of material around the insertionaxis is presented using Digital Image Correlation in a stable,plane-strain configuration. Insight into the shape of needles tominimise tissue trauma and generate interactions that wouldenable optimal steering conditions is provided. Needle tipswith an included bevel angle up to 40result in asymmetricdisplacement of the surrounding tissue phantom. Increasingthe included tip angle to 60results in more predictabledisplacement and strains that may enhance steering forces withlittle negative impact on the phantom.